Oxidative Stress in Hypo and Hyperthyroidism - Suchetha Kumari N.1*, Sandhya2 and K.M.Damodara Gowda 3 (Al Ameen Medical College, 2011)
Thyroid hormones from the thyroid gland are necessary for the normal development of body organs. It was demonstrated that NO participates in the regulation of thyroid function. NO brings about oxidation reactions which will produce free radicals, and can start chain reactions that damage cells. This leads to the production of ROS. These oxidants can damage cells by starting chemical chain reactions such as lipid peroxidation, or the oxidizing DNA or proteins. The oxidation status was assessed by measuring the level of nitric oxide, total antioxidants and the antioxidant enzyme, Super Oxide Dismutase (SOD) in the blood. All the data were analyzed by one-way ANOVA followed by paired t-test. The level of significance was considered at P> 0.05.Serum nitric oxide and total antioxidants were decreased significantly in hyperthyroidism and almost no change in hypothyroidism when compared to the normal levels. Further, erythrocyte super oxide dismutase (SOD) was significantly high in patients with hyperthyroidism and it is almost same in hypothyroidism and normal controls. The result indicates that the thyroid hormone has a pro-oxidant effect and increases the oxygen free radical production and hence the resultant decrease in antioxidant state in case of hyperthyroidism when compared to the normal and hypothyroidism.